PRODUKSI COCO-BIOFUEL DAN APLIKASINYA PADA MESIN DIESEL DENGAN SISTEM INJEKSI LANGSUNG - Soni Sisbudi Harsono; Mukhammad Fauzi; . Suhardi; Lilik Mulyantara (JURNAL AGROTEKNOLOGI, 2012)
This study is devoted to the performance and emission evaluation of automotive diesel engine as affected by coco biofuel utilization. The concentration of palm biodiesel used in the test was ranged from B0 (pure petro-diesel), B10, B20, B30, B50 and B100 (pure biodiesel). The engine performance was evaluated through torque, power, and specific fuelconsumption, while the emission was evaluated through carbon monoxide (CO), hydrocarbon (HC), particulate matter (PM), carbon dioxide (CO2), and NOx pollutants. The result shows that higher content of palm biodiesel can reduce the emission of CO, HC, PM, and CO2. It was found that the addition of biodiesel could increase the power and torque. Further more, NOx also decreased when the content of palm biodiesel increases, which is in contrast with those generally found in the previous non palm biodiesel studies.Keywords: palm oil biodiesel, petro-diesel, carbon monoxide, hydrocarbon, particulate, matter, O2,and NOx pollutants